2011
DOI: 10.1155/2011/126895
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Physiological Correlates of Irritability in Depression: Results from the Netherlands Study of Depression and Anxiety

Abstract: Objective. Irritable and nonirritable depressed patients differ on demographic and clinical characteristics. We investigated whether this extends to psychological and physiological measures. Method. We compared irritable and nonirritable unipolar depressed patients on symptomatology, personality, and (psycho)physiological measures (cortisol, cholesterol, and heart rate variability). Symptomatology was reassessed after one year, and we also compared depressed patients who were irritable or non-irritable at both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…In both sexes, irritability seems to be associated with more significant depressive symptoms. This finding is consistent with what was previously observed in a clinical population of adult patients with MDD seeking treatment (Perlis et al, 2009) and in a community sample (Verhoeven et al, 2011). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both sexes, irritability seems to be associated with more significant depressive symptoms. This finding is consistent with what was previously observed in a clinical population of adult patients with MDD seeking treatment (Perlis et al, 2009) and in a community sample (Verhoeven et al, 2011). …”
Section: Discussionsupporting
confidence: 92%
“…Earlier reports (Perlis et al, 2009; Verhoeven et al, 2011) have also observed that irritability in depressed patients is associated with anxiety symptoms, but these previous studies did not examine this association separately in men and women and in young adults. Our finding may be explained by the fact that irritability is a prominent symptom of GAD according to the DSM-IV (American Psychiatric Association, 2000) and that GAD alone, and, similarly, GAD co-occurring with depression, is more common among women than men (McLean et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…This is consistent with the finding in numerous clinical studies that a high proportion of adult patients in treatment for MDD have symptoms of irritability . It also ties in with the point made in the introduction that irritability might be a useful severity marker or a useful basis for subtyping adults with DSM‐IV MDD even if it is not a useful basis for expanding the definition of MDD. It might be the case that information about irritability has relevance for depression treatment.…”
Section: Discussionsupporting
confidence: 88%
“…A distinction must be made here between using irritability as a severity marker or a subtyping distinction among adults with DSM-IV MDD and using irritability to expand the definition of major depression. Whereas existing research suggests that irritability in MDD may serve as a severity marker in clinical samples [7,8] and have possible value as a diagnostic subtyping symptom, [4,8] we are unaware of previous evidence on the implications of allowing irritability to be used to expand the definition of adult MDD. Revising adult MDD criteria to include irritability might help offset some postulated gender bias in depression measurement, as sociocultural theories suggest that current diagnostic criteria might be insensitive to gender differences in affective expression due to men manifesting depression less than women in terms of sadness and loss of interest and more in terms of irritability.…”
Section: Introductionmentioning
confidence: 95%
“…Irritability has been conceptualized as being “easily annoyed and provoked to anger” and having “a mood dominated by poor control over temper” . It can range from subjective feelings and cognitions to overt expressions of anger . Irritability is part of human experience but some people are more prone to it because of their personality, temperament, or mental health condition .…”
Section: Introductionmentioning
confidence: 99%